Bouncing of a bubble at a liquid–liquid interface. Issue 7 (27th January 2017) - Singh, K. K.; Gebauer, F.; Bart, H.‐J.
Abstract : Significant industrial relevance of gas–liquid–liquid flows calls for understanding of their various aspects. This study focusing on one of the aspects, i.e., interaction of a single bubble with a liquid–liquid interface, is aimed at providing the experimental evidence of a hitherto unreported phenomenon of conditional bouncing of a bubble at the interface between two immiscible, initially quiescent liquids. Bouncing of the bubble is observed for two of the six pairs of the immiscible liquids used in the experiments. The data, obtained by conducting experiments with different pairs of the lighter and heavier liquid bubble diameters and rise heights, suggest that a bubble crossing a liquid–liquid interface is expected to bounce when its average velocity is less than a threshold value that depends on the interfacial tension between the two liquids and the viscosity of the heavier liquid. © 2017 American Institute of Chemical Engineers AIChE J, 63: 3150–3157, 2017